Uzbekistan : Second Agricultural Public Expenditure Review - Zorya, Sergiy; Gautam, Madhur; Tesfaye, Teklu; Babaev, Sandjar; Nazarov, Parkhod (World Bank, Washington, DC, 2021)
Public expenditures matter a lot for agricultural growth, food and nutrition security, sustainable food systems, and other interlinked developmental outcomes. The level of agricultural public spending is important as small budgets can rarely deliver results, let alone drive any transformation of the sector. Yet, global experience clearly shows that although greater spending on agriculture is important, it does not always guarantee better outcomes unless: (i) funds are allocated to the ‘right’ programs and functions, which help address market failures and deliver public goods (i.e., allocative efficiency); (ii) the right programs are being implemented well (i.e. implementation efficiency); and (iii) public expenditures are supported by market-friendly agricultural policies (i.e., no agricultural price distortions). Spending more on agriculture without making progress on all the above-mentioned conditions is not recommended, because higher public spending without progress on agricultural development could result in fiscal, inflation, exchange rate, and other macroeconomic risks, which would backfire on the agriculture sector itself in the medium to long run. The quality of public spending is, therefore, an important issue, which has become even more urgent during and in the aftermath of the COVID-19 crisis. The crisis required Uzbekistan to make substantial unforeseen public expenditures, which resulted in the larger public borrowing and lower fiscal space in the future. This report presents a review of Uzbekistan’s AgPER to contribute to the policy dialogue on the repurposing of public expenditures and getting more value for money. This is the second AgPER for Uzbekistan prepared by the World Bank in the last three years. The first AgPER was completed in 2019. It fed into the Agricultural Strategy, which was being prepared at that time and later approved in October 2019. It set the 2016-2018 baseline of agricultural public expenditures for the Agricultural Strategy, underpinning Annex 4, which presented the direction of the major repurposing of agricultural public expenditures by 2030. The expenditure repurposing encompassed the phasing out of direct subsidies coupled with production conditions and a move toward more efficient farm support instruments, such as climate-smart direct farm support and investments in general support services to increase the developmental impact of public expenditures. The first AgPER presented global lessons about the impacts of various types of agricultural public expenditures (for example, their functional composition) on developmental outcomes in the agriculture sector, which were considered in preparation of Annex 4 of the Agricultural Strategy.